Influence of Triple Diffusive Convection in Peristaltic Flow of Jeffrey Nanofluid Through Non-Uniform Channel - Asha, S. K.; Kallolikar, N. (Engineering Science & Technology, 2022)
In this investigation, we considered the effect of triple diffusive convection on peristaltic flow through a non-uniform Channel. We also considered the incompressible non-Newtonian Jeffrey nanofluid. On the assumption of a long wavelength and low Reynolds number, the governing equations were transformed into a non-dimensional form. The reduced non-dimensional highly nonlinear partial differential equations were solved using the Homotopy Perturbation Sumudu transformation method (HPSTM). The influence of different physical parameters on dimensionless velocity, pressure gradient, temperature, the concentration of salt 1 and salt 2, and volume fraction was graphically represented. The Dufour solutal Lewis number of salt 1 and salt 2 on the velocity profile increases. The Dufour solutal Lewis number and modified Dufour parameter of salt 1 rise on the nanoparticle volume fraction profile. It is found that the presence of the triple diffusing components with small diffusivity can change the convection in the system. The change in density in a triple diffusive is caused by the thermal and solutal diffusivities of two separate chemical species. So this study is applicable in engineering and scientific fields like geology, astrophysics, disposal of nuclear waste, deoxyribonucleic acid (DNA), and chemical engineering. This work is compared with the exact solution, and it is in good agreement with this method.